Օրվա պահեր արտահայտող բառերը Ղարաբաղի բարբառում - Ալթունյան, Էդիտա (Լիմուշ հրատ.)
Цель данной статьи – рассмотреть понятия утро, полдень, вечер, их соответствия и синонимические группы в карабахском диалекте, координируя всю семантическую структуру этих понятий, раскрывая их языковые и культурные ценности, с помощью которых выражаются духовные и биокультурные особенности диалектоязычных народов. В рамках исследования мы поставили перед собой задачу: выявить функциональные особенности этимологических анализов и семантических сдвигов ранее указанных единиц, что в свою очередь позволяет выяснить путь развития данных понятий, таким образом подтверждает использование армянского языка на территории Арцаха и языковое влияние на диалктические реалии. The aim of the article is to examine the concepts of «morning», «noon», «evening», their dialectal correspondences and synonymous groups in the Karabakh dialect by coordinating the whole semantic framework of these units, discovering their linguistic and cultural value, semantic analysis, by which the intellectual and biocultural features of the dialect-speaking people are expressed. In the framework of the research, we have put forward the task of revealing the functional features of the mentioned units by studying their etymological analyzes and semantic displacements, which gives an opportunity to find out the process of the development of the biography of those units, thus making the ancient use of the Armenian language and the linguistic influences of dialect in the territory of Artsakh factual. Հոդվածի նպատակն է քննության առնել առավոտ, կեսօր, իրիկնապահ հասկացությունները, դրանց բարբառային համապատասխանությունները և հոմանիշային խմբերը Ղարաբաղի բարբառում՝ այդ միավորների իմաստային ողջ շրջանակի համակարգմամբ, դրանց լեզվամշակութային արժեքի բացահայտմամբ, իմաստաբանական վերլուծություններով, որոնցով արտահայտվում են բարբառակիր ժողովրդի մտավոր և կենսամշակութային առանձնահատկությունները։
Keywords: Լեզվաբանություն